Raising brows : my story of building a billion-dollar beauty empire - Soare, Anastasia (Portfolio, 2025)
"From the founder of Anastasia Beverly Hills - an immigrant who built a global cosmetics brand from nothing - an inspiring memoir about believing in yourself and chasing what brings you joy An esthetician and single mother with no connections, Anastasia Soare risked her life escaping communist Romania to come to America. Raising Brows tells the remarkable story of how she built a billion-dollar beauty brand and went from watching Oprah's TV show to learn English, to shaping Oprah's eyebrows on the very same show years later. Anastasia disrupted the beauty industry by applying her art school training on the "golden ratio" of beauty to eyebrows. Helping women find harmony with their face, Anastasia put eyebrows on the map. She pioneered new makeup products and built a glittering roster of clients like Michelle Obama, Jennifer Lopez, Kim Kardashian, and Hailey Bieber. But beneath the glossy exterior, Anastasia's path wasn't easy. In this powerful memoir, she shares her extraordinary journey, putting her Romanian values of hard work, persistence, and optimism to the test in Los Angeles, ignoring the landlords and bank managers who laughed when she tried to open a salon focusing on brows. Anastasia's story serves as a powerful reminder that you can do anything you put your mind to so long as you are passionate and determined. As she says, "It's the love and effort we put into our pursuits and relationships that truly define our success.""-- Provided by publisher.